DAMPAK PERSEPSI BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DIVISI SDM DAN UMUM PT. SWABINA GATRA - YOGI ASLIAN, MAS (Jurnal Ilmu Manajemen (JIM), 2019)
PT. Swabina Gatra is a national private company incorporated in Semen Indonesia Group with a dedication to improving the quality of quality products in the business sector, among others: Labor supply services, security services, cleaning services, warehouse management, equipment maintenance, general trading, vehicle rental and drinking water manufacturers in "SWA" packaging. This study aims to examine and find out whether workload and work environment have an influence on the performance of HR and General division employees at PT. Swabina Gatra. This type of research is causality with a quantitative approach method. The sample in this study amounted to 47 respondents and the sampling technique was saturated samples. The statistical analysis used in this study was multiple linear regression with the help of the SPSS program. The results of this study can be known that workload has an influence on employee performance, the work environment has no influence on employee performance, workload and work environment simultaneously influencing employee performance. Keywords: employee performace; work environment; workload.